Assessing France's Joint Audit Requirement: Are Two Heads Better than One? - Francis, Jere R.; Richard, Chrystelle; Vanstraelen, Ann (Auditing : a journal of practice and theory, 2009)
We examine auditor choice for listed companies in France where two (joint) auditors are required by law. This unique setting creates more complex auditor choice than the typical Big 4/non-Big 4 dichotomy in other countries, and we study if a firm's ownership structure affects its auditor-pair choice as well the consequences on earning quality. The findings are consistent with agency theory and indicate that a Big 4 auditor (paired with a non-Big 4 auditor) is more likely to be used when there is greater information asymmetry (less family control and more diversified ownership structures), and that these associations are even stronger for firms with two Big 4 auditors conducting the joint audit. We also test if a firm's auditor-pair choice affects earnings quality and find that firms using one Big 4 auditor (paired with a non-Big 4 auditor) have smaller income-increasing abnormal accruals compared to firms that use no Big 4 auditors and, once again, find that this effect is even stronger for firms that use two Big 4 auditors.